Visual detection of turkey coronavirus RNA in tissues and feces by reverse-transcription loop-mediated isothermal amplification (RT-LAMP) with hydroxynaphthol blue dye - Cardoso, Tereza C. [UNESP]; Ferrari, Heitor F. [UNESP]; Bregano, Livia C. [UNESP]; Silva-Frade, Camila [UNESP]; Rosa, Ana Carolina G. [UNESP]; Andrade, Alexandre Lima de [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2010)
A sensitive reverse-transcription loop-mediated isothermal amplification (RI-LAMP) assay was developed for the rapid visual detection of turkey coronavirus (TCoV) infection The reaction is performed in one step in a single tube at 65 degrees C for 45 min with hydroxynaphthol blue (HNB) dye added prior to amplification The detection limit of the RI-LAMP assay was approximately 10(2) EID50/50 mu l TCoV genome and no cross-reaction with other avian viruses was observed The assay was evaluated further in tissue suspensions prepared from the ileum and ileum-caecal junctions of infected turkey embryos 100% of these samples were positive in the RI-LAMP assay All individual feces samples collected in the field were considered positive by both conventional RT-PCR and RI-LAMP In conclusion RI-LAMP with HNB dye was shown to be a sensitive simple assay for the rapid diagnosis of TCoV infection either directly from feces or in association with virus isolation methods (C) 2010 Elsevier Ltd All rights reserved
Keywords: Turkey coronavirus; Hydroxynaphthol blue; LAMP assay; Spike gene